THE DEPENDENCE OF THE GUM EFFICIENCY FROM THE FLOOR IN THE NORMAL TYPE OF CHEWING - K. Toncheva; D. Korol; D. Kindiy; R. Kozak; I. Skubiy (Ukrainian Medical Stomatological Academy, 2017)
The authors drew attention to the importance of the definition of chewing efficiency as one of the hallmarks of the quality of human health according to chew effectively - is a sign of proper care. Poorly chewed food entering the stomach, first of all leads to alterations in the body, which further causes the emergences and development of pathological processes inside and the whole system. Thus, the definition of chewing efficiency makes it possible to assess the performance of this function. The modern dental science actively implementing and using modern computer technology, one of these modern capabilities is a digital picture analysis test with chewing results, followed by statistical processing of data and the possibility of archiving. The goal of the authors was to determine the degree of relationship between gender and chewing efficiency by the method of chewing test by the author's methodology and set of data for comparison during researches in future. The study involved 60 people including 28 men and 32 women aged 17 to 25 years, average age was 18,25r. In our study we had used our own logic test preparation material and the procedure for healthy young people without defect of hard tissue of teeth and dentition. Samples for tests performed as colloid chewing mass agar-agar in the form of cylinders. The authors revealed that increasing number of pieces and reducing their space demonstrated high chewing efficiency and therefore better mastication of the food, as observed in the group of men. In the group of women authors noted fewer pieces and larger average area, indicating that less chewing efficiency and, consequently, eat worse treated. It was found that the overall effectiveness of chewing in men was higher by 15% compared with women. For the purpose of statistical analysis of the data the authors used the nonparametric Wilcoxon's method for dependent groups that allowed to confirm an alternative hypothesis on performance differences of the total number of fragments and their average area in groups of men and women. Considering to obtained numerical results, the authors concluded that the performance of the total number of pieces of chewing sample and the average area of the fragments are the most important markers of chewing efficiency. According to the study, which were confirmed statistically the relationship between sex and efficient grinding of food had been proven. The authors indicate the avenues for further researches, such as detailed numerical data on individual sample fractions chewing and application of the proposed method in groups of individuals with structural and functional disorders of the teeth-jaw system.